Case report: Clinical and immunohistochemical manifestations of suspected Sjogren's disease in a dog - Story, Brett D.; Thomasy, Sara M.; Randolph, Max W.; Vincek, Anna; Martins, Bianca; Mills, Erinn P.; Dear, Jonathan D.; Johnson, Eric G.; Jordan, Richard C.; Goldschmidt, Stephanie L.; Vapniarsky, Natalia (Frontiers in Veterinary Science, 2024)
Sjogren's disease, well-described in people, is rarely identified in veterinary species. In people, Sjogren's disease is one of the most common systemic autoimmune disorders with an incidence of 0.5% in the female population. The hallmark histopathologic finding of primary Sjogren's disease is lymphomononuclear cell infiltrates aggregating as periductal infiltrate in salivary glands. Sjogren's-like disease has been reported in a domestic shorthair cat and golden retriever dog. However, both lacked positive antinuclear antibody (ANA) titers and the dog showed no clinical evidence of dry eye disease. The following case report describes the clinical and immunohistochemical findings suggestive of Sjogren's disease in a 3-year-old spayed female German shepherd cross that was presented for medically refractory absolute dry eye, xerostomia confirmed with oral atropine response tests, and bilateral mandibular salivary gland enlargement. Routine topical lacrostimulants, anti-inflammatories, heterologous serum, ocular lubrication, and oral pilocarpine failed to improve clinical signs or tear production. The ANA titer at 1:160 was interpreted as positive, while the complete blood count and serum biochemistry panels were unremarkable. Head and neck ultrasound revealed bilateral moderately enlarged mandibular salivary glands with a hypoechoic, mottled echotexture consistent with sialoadenitis and regional lymphadenomegaly; thoracic radiography and abdominal ultrasonography were normal. In vivo confocal microscopy and spectral-domain optical coherence tomography of the cornea confirmed lipid keratopathy presumably secondary to corneal desiccation and steroid administration. Salivary gland histopathological and immunohistochemical analyses supported an immune-mediated etiology. Approximately 60% of the salivary section contained inflammatory cells replacing the glandular structures with a focus score of 12. Immunohistochemical markers CD3, CD204, CD79a, and CD20 were evaluated. The inflammatory infiltrate was a mixture of T-cells and macrophages with rare individual immunoreactive B-cells. CD3 and CD4+ T-cells were confirmed using immunohistochemistry and quantitative PCR, respectively. Clinical signs including ocular discharge and mandibular salivary gland enlargement markedly improved following oral immunomodulatory therapy with prednisone (1 mg/kg/d, tapered over 2 months) and long-term leflunomide (2 mg/kg/d). Ocular discomfort improved dramatically decreasing the need for topical lubricants; however, tear production failed to improve likely due to extensive lacrimal gland atrophy. The aim of this report is to increase awareness of Sjogren's disease in dogs and interpret the pathology involved.